2008
DOI: 10.1111/j.1523-5378.2008.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyclooxygenase2–ProstaglandinE2 Pathway on Helicobacter pylori‐Induced Urokinase‐Type Plasminogen Activator System in the Gastric Cancer Cells

Abstract: Our results indicated that COX2-PGE2 pathway may be involved in H. pylori-associated uPA and uPAR induction, and that COX-2 inhibitor or EP2 receptor antagonist may inhibit angiogenesis and tumor invasion via suppression of the uPA system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Furthermore, COX2 can induce angiogenesis via VEGF and b Wbroblast growth factor (bFGF) expression, and increases the metastatic potential by up-regulation of uPA and matrixmetallo-proteinase 2 (MMP2). These changes result in an increased tumourigenic potential and supports the hypothesis that COX2 over-expression plays a key role in the cancer transformation process (Iwamoto et al 2008).…”
Section: Cox Inhibitorssupporting
confidence: 79%
“…Furthermore, COX2 can induce angiogenesis via VEGF and b Wbroblast growth factor (bFGF) expression, and increases the metastatic potential by up-regulation of uPA and matrixmetallo-proteinase 2 (MMP2). These changes result in an increased tumourigenic potential and supports the hypothesis that COX2 over-expression plays a key role in the cancer transformation process (Iwamoto et al 2008).…”
Section: Cox Inhibitorssupporting
confidence: 79%
“…Chronic atrophic gastritis caused by H. pylori activates synthesis of growth factors, cytokines, and gastrin leading to elevated COX-2 expression [19]. Furthermore, CagA-positive H. pylori infection associates with COX-2 expression in human gastric cancer [20], and in gastric cancer cells H. pylori exposure elevates COX-2 expression [21]. H. pylori may thus play an important role in induction of COX-2 synthesis during chronic gastritis that is a precancerous condition for gastric cancer.…”
Section: Cox-in Human Gastric Carcinogenesismentioning
confidence: 99%
“…pylori has been related to induction of uPAR. Several in vitro studies have found that the expression of uPAR is upregulated in cancer and gastric epithelial cell lines when co-cultured with H. pylori (Guillemin, Salama, Tompkins, & Falkow, 2002;Sepulveda et al, 2002;El-Etr, Mueller, Tompkins, Falkow, & Merrell, 2004;Iwamoto et al, 2005;Kim et al, 2005;Kim et al, 2007;Iwamoto, Mizokami, Takahashi, Matsuoka, & Matsuzaki, 2008). This phenomenon has also been documented in vivo, specifically in non-neoplastic tissue (adjacent to the tumor growth) obtained from GC patients (Alpízar-Alpízar et al, 2010), as well as in gastric biopsies from patients that have no cancer but are infected with the bacterium (Kenny et al, 2008).…”
Section: Plasminogen Activation System and Helicobacter Pylorimentioning
confidence: 83%